2000
DOI: 10.1165/ajrcmb.23.3.4002
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Downstream Genes of Tumor Suppressor PTEN in Lung Cancer Cells by Complementary DNA Microarray

Abstract: The phosphatase and tensin homology deleted on chromosome 10 (PTEN) is a tumor suppressor gene with sequence homology to tyrosine phosphatases and the cytoskeletal proteins tensin and auxilin. PTEN has recently been shown to inhibit cell migration and the spreading and formation of focal adhesions. This study investigated the role of PTEN in carcinoma invasion in a lung-cancer cell line and examined the downstream genes regulated by PTEN. We have previously established a cell-line model in human lung adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Of 709 genes identified to be suppressed by Pten overexpression or up-regulated due to Pten deficiency in the above mentioned papers, only Cyclin B1 (27,30) and MYBL2 (25,27) showed consistent results by more than one laboratory; whereas totally opposing results about Drg-1 were reported (25,27,31). Several possibilities could explain these discrepancies.…”
Section: Discussionmentioning
confidence: 96%
“…Of 709 genes identified to be suppressed by Pten overexpression or up-regulated due to Pten deficiency in the above mentioned papers, only Cyclin B1 (27,30) and MYBL2 (25,27) showed consistent results by more than one laboratory; whereas totally opposing results about Drg-1 were reported (25,27,31). Several possibilities could explain these discrepancies.…”
Section: Discussionmentioning
confidence: 96%
“…It is reported that both IL4 and IL13 share signalling events in human colon carcinoma cell lines (HT29 and WiDr), and that both IL13 and IL4 induce phosphorylation of IL4 STAT (STAT6) (Murata et al, 1996;Terabe et al, 2000). The leukocyte elastase inhibitor is one of the possible target genes of PTEN (Hong et al, 2000). Up-regulation of leukocyte elastase inhibitor is thought to protect cancer cells from damage by immune cells, so that weakness of the IL13 -IL4 Stat signalling pathway would allow cancer cells to escape from the immune response of the host.…”
Section: Genes Related To Immunitymentioning
confidence: 99%
“…Established cell lines, tumor derived primary cell cultures, and immunopurified cells procured through tissue dissociation and cell sorting have been studied as surrogates. [10][11][12][13][14][15][16] However, such studies are limited by flaws related to artificial in vitro conditions, prolonged propagation, and/or stressful purification procedures, all of which are expected to induce marked changes in the transcriptome, as cells are deprived from their natural metabolic, paracrine, endocrine and immune milieu, and lose critical adhesive interactions affecting their function in the tumor microenvironment.…”
mentioning
confidence: 99%